Methodology of Quran Fehmi of Shah Waliullah Dehlvi - Nazia, Uzma Zareen; Rafique, Sohail (sourcecoder, 2023)
The article revolves around the methodology of Quranic teachings by Shah Waliullah Dehlvi (1703-1763 AD) in south of Asia, especially, in India. Persian was the court language as well as the medium of instruction over centuries. Shah Waliullah played an important role in reconstructing the foundation of Islamic society. The 1st easy Persian translation of the holy Qur’an is his renowned work and, he also introduced simplified ways of learning the Islamic teachings to Muslims. The main objective of writing such research is to highlight the efforts of the awesome exegete of Quran, Shah Waliullah Dehlvi, the educator of a wide number of Muslims in India.